Determination of seismic isolation effects on irregular RC buildings using friction pendulums. (December 2021) - Meral, Emrah
Abstract: This study aims to evaluate influences of isolation made using friction pendulum type isolators on seismic behavior of irregular mid-rise RC frame buildings without shear walls. For this at first, a 4-storey 3D reference building model which have no irregularity is designed as residential building. Afterwards, models including heavy overhang, short column and soft storey irregularities are created through the reference building. A total of 88 nonlinear time history analyses of regular and irregular building models subjected to 11 pairs of ground motion records are performed for non-isolated and isolated cases. There has been a significant reduction in base shear ratios for isolated reference and irregular buildings. Roof drift ratios of isolated-base models are generally higher compared to fixed-base models for both regular and irregular buildings. Unlike the results of roof displacement demands, lower average interstorey drift ratios have been obtained for especially isolated reference and heavy overhang buildings. Evaluations on the effects of the isolation for floor accelerations, interstorey drift ratio (IDR) profiles and damages of structural elements are also given in the paper. This study emphasizes that advances are made in terms of behavior against earthquakes for irregular buildings thanks to isolation.